THU0614 Fidelity of an intervention to increase physical activity in older adults with chronic pain: analysis of audio-recorded consultations from the ipopp pilot trial. (15th June 2017) - Jinks, C; Proctor, J; Healey, EL; McBeth, J; Graham, CA Chew; ,
Abstract : Background: Physical activity levels are low in people >65 years and those with chronic musculoskeletal pain, yet increased physical activity can lead to reduced pain. Walking is acceptable to older people with pain, but interventions to increase walking in this population are untested. The iPOPP pilot trial investigated feasibility and acceptability of a walking intervention delivered by trained Health Care Assistants (HCAs) in 4 general practices in an individually randomised three arm trial (usual primary care, pedometer only and iPOPP, n=50 each arm). The iPOPP intervention comprised two consultations (1 week apart) and 8 weekly follow-up prompts (postcard, email or text). Objectives: To investigate fidelity of the iPOPP intervention to inform design of a full-scale randomised controlled trial. Methods: HCAs were asked to record 6 consultations (3 participants, first and second consultation). A fidelity checklist was developed (aligned to HCA training) and included activities expected (pedometer, user guide, walking diary, pain toolkit given; discussion of walking behaviour and barriers; action planning to develop walking goals; review of progress; positive feedback; revision of goals; relapse prevention strategies; and, preference for weekly prompts). Activities were scored as "Yes" (completed as intended), "partial" (some evidence), "No" (no evidence) or "NA" (not applicable). The checklist was applied to one recording (JP, CCG, CJ). Minor amendments clarified interpretation of checklist headings before application to 3 more recordings (JP, CCG). JP then scored remaining recordings (n=14). Results: 3 HCAs recorded 18 consultations (9 first, 9 second). Most first consultations did not use the allocated 30 minutes (average 14 minutes). The pedometer, user guide, walking diary and pain toolkit were all given but there was a lack of explanation of the pain toolkit. Evidence of the benefits of walking on pain was well delivered (N=8), motivators to walk and goals were discussed in all 9, with goals set in 7. Barriers to walking were not always discussed (N=4) exploration of maintenance strategies lacking, especially with those patients who perceived themselves as already physically active. All HCAs arranged a second consultation within one week which were brief (average 6.5 minutes) and focused mainly on use of the pedometer. Patient goals were partially re-visited (N=7) and barriers to walking partially addressed (N=5). Maintenance strategies were not discussed (N=8). Conclusions: Core iPOPP intervention components were well delivered. However we have identified areas to optimise ahead of a full-scale trial (how to discuss barriers to walking and maintenance strategies, development of motivational interviewing skills to support revision of goals, HCA knowledge of local activities). These findings will be triangulated with data from interviews with HCAs and participants to provide further evidence of the feasibility and acceptability of the iPOPP intervention. Acknowledgements: Keele Clinical Trials Unit, Keele University supported the trial. ELH, CJ, and CCG are part funded by the NIHR Collaborations for Leadership in Applied Health Research and Care West Midlands. The views expressed in this paper are those of the author(s) and not necessarily those of the NHS, the NIHR, or the Department of Health. Disclosure of Interest: None declared